STRATEGI PENGELOLAAN BADAN USAHA MILIK DESA (BUMDES) DALAM MEMBERDAYAKAN EKONOMI MASYARAKAT - rudiamir rudi (JAPPA: Jurnal Andragogi Pedagogi dan Pemberdayaan Masyarakat, 2022)
The establishment of Village-Owned Enterprises is the most appropriate way for village governments to be able to develop the economy of their communities, because it is an institution formed by village communities supported by the village government to foster and manage business units that can contribute to economic development in the village. This research uses a qualitative approach with a type of case study research. Based on the results of the research that has been carried out, it can be concluded that the Management of Village-Owned Enterprises in Pakkanna Village, Tanasitolo District, Wajo Regency runs according to governance standards by referring to management indicators, namely: Planning is carried out in accordance with procedures aimed at maximizing the management of business units. Organizing, its position outside the organizational structure of the village government, theinvolvement of each personnel in the management according to their respective abilities and prioritizing those who already have similar work experience. At the mobilization stage, there is always guidance, advice and orders from the management in order to be able to work optimally in carrying out tasks in order to achieve predetermined goals. Supervision is carried out to ensure that activities run in accordance with the established plan carried out by a predetermined team through a meeting of the management with elements of the Village government, although in reality there is still a lack of involvement from the village government and even the community in supervising Village-Owned Enterprises.